1997
DOI: 10.1038/sj.ejcn.1600429
|View full text |Cite
|
Sign up to set email alerts
|

Women with insulin-dependent diabetes mellitus (IDDM) complicated by eating disorders are at risk for exacerbated alterations in lipid metabolism

Abstract: Objective: To examine lipid parameters that are affected in women with insulin-dependent diabetes mellitus (IDDM) who engaged in disordered eating behaviours. Design: Randomized, unmatched. Setting: Tertiary care. Subjects: Ninety women (18±46 y) with IDDM. Interventions: Classi®cation of subjects based on severity of eating disorder: clinical (n 14), subclinical (n 13) and control (n 63). Blood was analysed for glycosylated haemoglobin (HbA 1c ) and serum for triglycerides and cholesterol. Carotenoid and toco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As AN-B eat foods rich in carbohydrate and fat (and thus rich in Chol) during the binge episodes, this could provide a further contribution to the higher Chol concentration seen in these subjects (Zoppi et al 1993;Sullivan et al 1998). Other studies have also suggested a relationship between this bulimic behaviour and hypercholesterolaemia (Crisp et al 1967;Affenito et al 1997;Case et al 1999). It could be argued that purging does not lead to absorption of the food consumed, but it has been shown previously that a substantial amount of energy is absorbed despite vomiting (Kaye et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…As AN-B eat foods rich in carbohydrate and fat (and thus rich in Chol) during the binge episodes, this could provide a further contribution to the higher Chol concentration seen in these subjects (Zoppi et al 1993;Sullivan et al 1998). Other studies have also suggested a relationship between this bulimic behaviour and hypercholesterolaemia (Crisp et al 1967;Affenito et al 1997;Case et al 1999). It could be argued that purging does not lead to absorption of the food consumed, but it has been shown previously that a substantial amount of energy is absorbed despite vomiting (Kaye et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…The BULIT-R DSED, and EDI-3 were examined by the authors, a psychologist diabetes educator, and a psychologist with type 1 diabetes to identify questions that could be answered affirmatively in the context of diabetes self-management behaviors. “Do you feel you have control over the amount of food you consume?” and “I eat a lot of food when I'm not even hungry” are BULIT-R questions (used in studies by Affenito et al [17,18]) that directly relate to the diabetes care regimen: the former by prescription of dietary restraint and the latter by use of exogenous insulin. A later question, “I feel that food controls my life,” could be endorsed by any individual with diabetes.…”
Section: Measurement Of Deb and Eating Disordersmentioning
confidence: 99%
“…More recent cross-sectional studies have demonstrated a positive association between elevated A1C and diagnosable eating disorders (2), subclinical DEB (8), and intentional insulin omission (1). The presence of diagnosable eating disorders and behavior categorized as subclinical DEB has been associated with increases in retinopathy (15), neuropathy (16), transient lipid abnormalities (17), hospitalizations for diabetic ketoacidosis (6), and poor short-term metabolic control (1,6,8,18). Studies assessing the association of DEB and eating disorders with long-term metabolic control have produced mixed results (6,1922).…”
mentioning
confidence: 99%
“…31 Each of these can independently increase the risk of long-term diabetes-related complications, affecting multiple body systems.…”
Section: Clinical Consequencesmentioning
confidence: 99%